TROUT HATCHERIES IN JAMMU AND KASHMIR: REVIEWING STATUS, CHALLENGES, AND SUSTAINABLE MANAGEMENT - Arif Hussain Pandith; NaoremRojita Devi (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2024)
Trout hatcheries in Jammu and Kashmir have an important role in the global recreational fishing industry and in the preservation and management of aquatic environments. The present status of trout hatcheries is summarized in this review study, with an emphasis on the historical relevance, species diversity, breeding methods, economic opportunities, current problems, developments, conservation efforts, disease management and possible further orientations of the industry. We look at a number of topics, such as disease control, environmental factors, breeding methods, and sustainable practices. This work attempts to offer ideas for enhancing trout fishery and hatchery operations and guaranteeing the long-term sustainability of the trout population in Jammu and Kashmir by reviewing the literature and local efforts that have already been written. Additionally, it provides recommendations for ways to improve the sustainability and efficacy of these efforts. This review investigates the inherent advantages of trout fish in Jammu and Kashmir, focusing on their importance, problems, ecological value, opportunities for sustainable development, and the overall dangers to their survival.